Innovation to Immune: Empirical Evidence From COVID-19 Focused Enterprise Surveys - Khan, Karamat; Liu, Sheng; Xiong, Baowei; Zhang, Leihao; Li, Chuntao (Frontiers in Psychology, 2022)
The recent COVID-19 crisis caught many by surprise. Yet some firms were better prepared to weather the downturn than others. Using a comprehensive data set that observes over 15,000 firms in 27 countries, including several developing countries, shortly before and after the pandemic, we document that pre-crisis innovation affected firm’s survival odds and performance thereafter. The results show that innovative firms are less likely to close and perform better than non-innovators during the pandemic crisis. Innovative firms are also more optimistic about the future than non-innovators. Our results further indicate that firm’s adaptability mediates the relationship between innovation and survival outcomes. The study finding shows that innovative firms are more likely to introduce new products, remote work arrangements, increase delivery, pivoting, and online activities than non-innovators during the pandemic crisis.